Effect of Native Trichoderma as Seed Treatment on Germination and Seedling Performance of Lentil Under Biotic and Abiotic Stress Conditions (SAARC Journal of Agriculture, 2023)
Physiological and water stress conditions substantially impede seed germination and the establishment of plant population. In 2020, a study was conducted in a completely randomized design (CRD) to identify potential Trichoderma strains that could alleviate physiological and water stress in germinating seeds. To create physiological stress, seeds were kept in an incubator at high relative humidity (90%) and temperature (40ºC) for 20 days. Similarly, to induce water stress on germinating seeds, Polyethylene glycol (PEG) was applied in four concentrations (0, 5, 10, and 15%). Nine different isolates of Trichoderma were isolated from forest and agricultural soil and conidial suspension was applied to lentil seeds to deposit 107cfu per gram of seeds. For each treatment, a total of one hundred seeds were placed on three layered moist blotter paper and incubated at 25±2°C. Germination was measured after every 24 hours. Under stress conditions, seeds treated with Trichoderma exhibited enhanced germination, root and shoot length, dry and fresh weight of root and shoot of seedlings as compared to untreated seeds. Highest seed germination under physiological stress and water stress was observed with Trichoderma isolates T87, Forest soil and T62, Darchula respectively. Isolate T87, Forest soil demonstrated the highest vigor index of seedlings in stress conditions. Seed treated with Trichoderma isolates also displayed significant improvement in germination under biotic stress induced by Sclerotium rolfsii. Trichoderma isolate T31, Banke showed highest germination under biotic stress. These findings highlight the potential of Trichoderma to enhance plant resilience and promote healthier growth under challenging environmental conditions.SAARC J. Agric., 21(2): 145-156 (2023)